Age pattern of gestational arrest in India and its regions: Evidence from NFHS-4 (2015–2016). (February 2021) - Singh, Mayank; Shekhar, Chander; Patel, Priyanka; Meitei, Wahengbam Bigyananda
Highlights: India indicates a higher rate of miscarriage among women age 15–19 years and age 35+. Central and the western regions showed a higher risk of abortion to women age 15–19 years. Half of the miscarriages and abortions occur during 8–10 weeks and 6–9 weeks of gestation. 1 in every 10 abortions and 1 in every 5 miscarriages occurred after the 1st semester. Abstract: Introduction: Pregnancy loss is a public health issue throughout the world. Miscarriage and induced abortion are the two main dimensions of pregnancy loss. The prevalence of early pregnancy loss due to miscarriage and abortion is mostly unknown due to the lack of early registration of pregnancies in most places, and especially in low- and middle-income countries. In a country like India, not enough attempts have been made to recognize pregnancy loss by weeks of gestational age. Objective: This study aims to know about the age-pattern of gestational termination using the calendar information from the fourth round of the National Family Health Survey. Statistical Methods: A generalized linear model with a binomial distribution assumption and Kaplan-Meier survival model with left truncation was used for statistical analysis. Results: The age-pattern of miscarriage produces a vertical convex shape curve when age is drawn at y-axis and the miscarriage rate at x-axis. There is a high relative risk of miscarriage to women age below 20 years and age 35 years onwards, whereas abortion risk was high among women age 30 and above years. Among women age 15–19 years, the abortion rate at 27 abortions per thousand pregnancies was the highest in the northeast region, and the miscarriage rate at 67 miscarriages per thousand pregnancies was estimated to be the highest in the western region among all the regions. A sizeable proportion of miscarriages and induced abortions also occurred in the second trimester and all the region. Conclusion: This article brings out that miscarriage is more commonly prevalent among women in the adolescence age 15–19 years and in the latter half of the reproductive span, whereas the incidence of abortion increases with age. The western and the northeast regions registered maximum miscarriage and abortion rates among women age 15–19, respectively. The central region as a whole showed the highest rate of miscarriage, whereas the abortion rate was the highest in the northeast region in India. The findings of the study will be beneficial in making appropriate policy provisions for postponing pregnancies among women in their adolescence and preventing the occurrence of miscarriages among more vulnerable age groups of women and regions by providing a complete package of high-quality antenatal care services.